Pengaruh Perceived Quality Dan Country Of Origin Effect Terhadap Niat Beli Xiaomi Smartphone - Yuni Puspita Sari (Universitas Negeri Surabaya, 2018)
Xiaomi smartphone is a smartphone vendors from China newly entered the smartphone market in Indonesia, in contrast to the smartphone with low price and low quality. Xiaomi markets its products with a premium price and high quality products, positioning as a brand management newcomer. This study aims to analyze and discuss the influence of perceived quality and country of origin effect of the Xiaomi smartphone purchase intention (studies in the visitors of Plaza Marina Surabaya). The population in this study is a person aged 19-50 years old who is visiting Plaza Marina Surabaya. In this study, researcher used 220 samples. Sampling method is a non-probability sampling. Data were analyzed using multiple linear regression. In multiple linear regression analysis results show the influence of variables perceived quality and country of origin effect for the purchase intention in the show of the value of Adjusted R Square of 0.407. From the results of the t test that has been done can be seen that the variable perceived quality and country of origin effect has a significant influence partially on the purchase intention.